Robinson Crusoe / Wałkuski ; Państwowy Teatr Lalka. - Wałkuski, Wiesław (1956- ). ([wydawca nieznany], 1993)
Plakat premiery 14.02.1994 r. Na plakacie twarz mężczyzny. Nazwisko autora przy lewej krawędzi.